2018
DOI: 10.1007/s10652-018-9645-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics of a periodically wind-forced small and narrow stratified basin: a large-eddy simulation experiment

Abstract: Ulloa et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 78 publications
(135 reference statements)
3
21
1
Order By: Relevance
“…Thus, we suggest that a turbulent bottom boundary layer driven by the seiche-associated currents was the major source of mixing, dissipation, and damping of the basin-scale oscillations. In sloping bottom basins as Porce II, basin-scale circulations associated with the internal waves can accelerate the flow close to the boundaries and favor the formation of supercritical shear layers, which, in turn, induce mixing around the metalimnetic region that intersects the lake boundary (Ulloa, et al, 2018). Direct measurements of turbulent dissipation (Román-Botero, et al, 2017) also showed that during periods of dominant basin-scale internal waves activity in Porce II, there was a strongly stratified turbulence at the interior (far from the boundaries), characteristic of low dissipation, in contrast with the high-isotropic turbulence induced by the density plumes during flood events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we suggest that a turbulent bottom boundary layer driven by the seiche-associated currents was the major source of mixing, dissipation, and damping of the basin-scale oscillations. In sloping bottom basins as Porce II, basin-scale circulations associated with the internal waves can accelerate the flow close to the boundaries and favor the formation of supercritical shear layers, which, in turn, induce mixing around the metalimnetic region that intersects the lake boundary (Ulloa, et al, 2018). Direct measurements of turbulent dissipation (Román-Botero, et al, 2017) also showed that during periods of dominant basin-scale internal waves activity in Porce II, there was a strongly stratified turbulence at the interior (far from the boundaries), characteristic of low dissipation, in contrast with the high-isotropic turbulence induced by the density plumes during flood events.…”
Section: Discussionmentioning
confidence: 99%
“…The natural modes are classified depending on the number of nodal points they have in the horizontal (j) and vertical (i) directions as ViHj ( Figure 1S, https://www.raccefyn.co/ index.php/raccefyn/article/downloadSuppFile/799/3895). The most commonly observed vertical baroclinic response is the V1 (Mortimer, 1953); however, higher vertical modes are not unusual (e.g., Wiegand & Chamberlain, 1987;Vidal, et al, 2005;Vidal & Casamitjana, 2007;Pannard, et al, 2011;Lorrai, et al, 2011;Ulloa, et al, 2018). The difference in the spatial structure of the modes leads to advection and mixing in different locations and, thus, it can drive mixing and turbulence at specific zones of the water column where high shear occurs (Wiegand & Chamberlain, 1987;MacIntyre, et al, 1999;Hondzo & Haider, 2005;Henderson, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seiches cause a wide spectrum of temporal fluctuations of all thermodynamic, hydrodynamic, and biogeochemical quantities in lakes, with maximal magnitudes in thermocline and profound secondary circulations at shores (Ulloa et al, 2019). A large number of models has been developed (e.g., Horn et al, 1986;Kirillin et al, 2015;Lemmin et al, 2005;Rueda & Schladow, 2002) specifically for simulation of seiche currents, based on both layer-wise and continuous representation of vertical density stratification.…”
Section: Introductionmentioning
confidence: 99%
“…Typically those models have not been coupled to turbulence closures and thermodynamic models, in order to represent effect of seiches on vertical mixing. Hence, so far two branches of lake modeling have been developing almost independently, namely, 1-D thermodynamic models and internal wave models (in this paper we do not discuss fully 3-D lake models (e.g., Delandmeter et al, 2018;Laval et al, 2003;Tsvetova, 1999;Ulloa et al, 2019) that explicitly reproduce wide range of circulation modes and interaction between hydrodynamic and thermodynamic variables). This paper strives to develop a computationally cheap extension to 1-D k − model, explicitly reproducing dominant seiche modes in momentum equations.…”
Section: Introductionmentioning
confidence: 99%